(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
From the beginning, the main purpose for establishing public schools in the United States was to prepare future generations for democratic citizenship particular to a new and experimental republic. Citizenship under non-democratic rule would not require education beyond what parents and community could instruct children about their place in society and their relationship to the ruling authority. But citizens of a democracy require formal schooling as they are, in theory, the ruling authorities and must therefore receive the knowledge (reading and writing and some classical history) and attitudes (vigilance against those who would seek political office for corrupt purposes) of leadership. This was Thomas Jefferson’s dream for the creation of a “natural aristocracy”. These most talented sons [sic] from all social classes, having proved their worth through success in formal schooling, would govern on the basis of virtue and merit rather than birth and wealth. Influenced by Plato’s utopian proposal for education, as well as other ideas central to classical liberalism, Jefferson recognized that to prevent the political ascendancy of a hereditary aristocracy, more than just the wealthy had to be educated. At the same time, all citizens should be able to exercise their responsibilities for electing leaders and approving legislation through access to the free marketplace of ideas where men [sic] could discuss and rationally consider the best course of action. He proposed a meritocratic form of promotion into higher education and preparation for political office. However, as Joel Spring observes, “the details of Jefferson’s plan are not as important as the idea, which has become ingrained in American social thought, that [public] schooling is the best means of identifying democratic leadership”